(untitled) (MAUSAM, 1952)
In this paper a modified parcel method of analysis of tephigrams is discussed. The method takes account of the entrainment of environmental air by the cloud air and the integrated effect of lighting air parcels from all levels in the “layer of instability”. An attempt has also been made in the modified parcel method to take account of a few other factors, viz., freeing level and shear vector. Some worked out examples by the use of the modified parcel method have been examined for Indian conditions and it has been shown that a fair degree of success cab be obtained by this method, if judiciously applied.